Giant leap for Namibian agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Giant leap for Namibian agriculture , Namibian Economist, May 2002 AGRA is Namibia´s only on-line agriculture trading facility, offering livestock sales, general information on agriculture prices, a genetics library and movable goods.